The influence of education level on voter behaviour in the 2024 presidential and vice-presidential election in Jambi - Pratiwi, Cholillah Suci; Muhammad, Hatta Abdi; Elsi, Sutri Destemi; Suryono, Muhammad Vicky Afris (Universitas Negeri Yogyakarta, 2025)
Educational attainment significantly influences voting behaviour in presidential elections, particularly in Jambi City. This study investigates the effect of formal education on voter behaviour during the 2024 presidential election and explores the behavioural patterns adopted by voters, including sociological, psychological, and rational approaches. It also assesses how education influences voter preferences and participation and its broader implications for local political dynamics. Employing a quantitative research design, data were collected through questionnaires distributed to voters in Jambi City. The findings reveal that higher levels of education are strongly associated with more informed and rational voting decisions. Formal and informal educational experiences enhance voters' political awareness and engagement. Moreover, voter behaviour in Jambi City reflects a combination of sociological influences, psychological dispositions, and rational considerations. This research contributes to a deeper understanding of the interplay between education and electoral behaviour, offering insights into the nature of democratic participation in regional contexts. The study also provides policy-relevant recommendations to promote inclusive voter engagement across all educational backgrounds.